Best linear unbiased estimates of growth for different environmental factors in Landrace and desi crossbreds - Gaur, G K; Chabbra, A K; Paul, Satya (The Indian Journal of Animal Sciences, 2012)
The records on 918 crossbred piglets (50% Landrace + 50% desi), progeny of 39 sires, over a period of 8 years from 1987 to 1994, maintained at the Livestock Production Research (Pigs) were used in this study to determine the influence of various environmental factors on growth using maximum likelihood (ML) procedure. Body weight of piglets were recorded at birth and thereafter at one-week-interval up to weaning (8 week). Growth in different weeks was estimated from the recorded weights. The prior heritability estimates used in ML analysis were obtained from the same data. Generation had significant effect on growth from first to fourth week and thereafter, at seventh week of age. Effect of sex and age at farrowing was nonsignificant at different ages. Season of birth affected growth at first, fourth, fifth and eighth week. Effect of litter size and parity was significant on growth almost up to fifth week. Inbreeding had no effect on growth in most of the weeks. Piglets born in later generations had higher growth. Generation 1 showed lowest growth almost in most of the weeks except in third and sixth week. September, October and November were more favourable conditions for sows to produce maximum amount of milk and for piglets to achieve highest growth. Piglets born in smaller litters received better growth in most of the weeks than those born in larger litters. Growth in second, third and fifth week was highest in piglets of third parity sows followed by those of second and first parity. Though effect of inbreeding was nonsignificant at most of the weeks, however, non-inbreed piglets had higher growth than those of inbreds.